UiO-67-SO2-coated ANF fiber aerogel as well as preparation method and application thereof

By uniformly loading UiO-67-SO2 on the surface of the ANF fiber, a UiO-67-SO2@ANF fiber aerogel with a three-dimensional hierarchical pore structure is formed, which solves the problems of uneven mesopore distribution and poor mechanical properties of existing MOF materials. , achieving high CO2 adsorption capacity and excellent mechanical properties.

CN119327430AActive Publication Date: 2025-01-21QINGDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411493156.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing MOF materials have problems such as uneven mesoporous distribution, poor mechanical properties, and low CO2 adsorption capacity, which is difficult to meet the needs of high-performance CO2 adsorbents in the industrial field.

Method used

UiO-67-SO2@ANF fiber aerogel was used to prepare aramid nanofibers through high-pressure homogenization method, and phosphoric acid treatment was used to promote UiO-67-SO2 to be uniformly loaded on the surface of ANF to form a three-dimensional hierarchical pore structure to improve CO2 adsorption. capacity.

Benefits of technology

The UiO-67-SO2@ANF fiber aerogel has excellent compression resilience and high CO2 adsorption capacity, and can maintain its intact shape after 800 compression-rebound experiments, significantly improving the CO2 adsorption efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327430A_ABST
    Figure CN119327430A_ABST
Patent Text Reader

Abstract

The invention discloses UiO-67-SO2 (at) ANF fiber aerogel and a preparation method and application thereof.The UiO-67-SO2 (at) ANF fiber aerogel comprises an MOF precursor and aramid nanofiber ANF, the MOF precursor comprises zircon salt and dibenzo [b, d] thiophene-3, 7-dicarboxylic acid-5, 5-diketone H2DTDAO, and the aramid nanofiber ANF is prepared from the zircon salt and dibenzo [b, d] thiophene-3, 7-dicarboxylic acid-5, 5-diketone H2DTDAO; the mass ratio of the zirconium salt to the H2DTDAO to the ANF is (0.8 to 1.2) to (1.8 to 2.2) to (0.8 to 1.2); the specific surface area of the UiO-67-SO2-coated ANF fiber aerogel is 670.29 m < 2 > / g, the pore volume is 0.501 cm < 3 > / g, and the average pore size is 0.472 nm. According to the invention, a large amount of MOF can be uniformly loaded on the surface of the ANF fiber, and the UiO-66-SO2-coated ANF fiber aerogel disclosed by the invention has excellent compression resilience and a three-dimensional hierarchical pore structure, and can effectively improve the CO2 adsorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fiber aerogels, and in particular relates to a UiO-67-SO2@ANF fiber aerogel and a preparation method and application thereof. Background Art

[0002] Faced with the continued growth of global greenhouse gas emissions and the intensification of climate warming, in-depth and extensive research has been carried out on CO2 capture technology at home and abroad. Metal organic frameworks (MOFs) have been widely reported and applied to CO2 capture due to their excellent structural characteristics such as high specific surface area, high porosity, adjustable pore size, and easy surface functionalization. However, in order for MOFs to truly approach or meet the demand for high-performance CO2 adsorbents in the industrial field, the following problems still need to be solved: (1) How to accelerate the gas mass transfer performance of MOF and expand its pore structure and compression elasticity to achieve efficient fluidity and mass transfer efficiency of CO2 gas molecules inside it; (2) How to regulate the physical and chemical microenvironment of MOF to enhance its affinity for CO2, thereby achieving high CO2 adsorption capacity and high CO2 adsorption selectivity.

[0003] Therefore, there is an urgent need to develop a new MOF material to solve the defects of existing MOF materials such as uneven mesopore distribution, poor mechanical properties, and low CO2 adsorption capacity. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a UiO-67-SO2@ANF fiber aerogel and a preparation method and application thereof. The present invention can load MOF uniformly and in large quantities on the surface of ANF fibers. The UiO-66-SO2@ANF fiber aerogel of the present invention has excellent compression resilience and a three-dimensional multi-level pore structure, which can effectively improve the CO2 adsorption capacity.

[0005] To this end, the present invention provides a UiO-67-SO2@ANF fiber aerogel, comprising: a MOF precursor and aramid nanofiber ANF, wherein the MOF precursor comprises a zirconium salt and dibenzo[b,d]thiophene-3,7-dicarboxylic acid-5,5-dione H2DTDAO; the mass ratio of the zirconium salt, H2DTDAO and ANF is (0.8-1.2): (1.8-2.2): (0.8-1.2); The specific surface area of ​​the UIO-67-SO2@ANF fiber aerogel is 500-700 m 2 / g, pore volume is 0.5-0.8cm 3 / g, and the average pore size is 0.4-1nm.

[0006] The present invention also provides a method for preparing the UiO-67-SO2@ANF fiber aerogel, comprising: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Cut the aramid fibrils into pieces, add them into an alkaline solution, reflux them in a constant temperature water bath, and after the solution is cooled, filter and wash the solution with distilled water until it is neutral to obtain an aramid fibril solution; (1.2) High-pressure homogenization treatment: using a high-pressure homogenizer to treat the aramid fibril solution to obtain an aramid nanofiber solution; filtering the aramid nanofiber solution to remove water to obtain aramid nanofibers; (2) Preparation of ANF aqueous dispersion Phosphoric acid PA treatment: adding the aramid nanofibers to the PA solution and stirring under water bath conditions; then washing the solution with distilled water until it is neutral and preparing it into an ANF aqueous dispersion; (3) Preparation of UiO-67- SO2@ANF fiber aerogel (3.1) placing the ANF aqueous dispersion in N, N-dimethylformamide (DMF) to prepare an ANF / DMF dispersion; (3.2) adding zirconium salt to the ANF / DMF dispersion and stirring until it is completely dissolved; then adding H2DTDAO and trifluoroacetic acid TFA and continuing to stir to obtain a mixed solution; (3.3) transferring the mixed solution to a reactor for reaction, and after the reaction is completed and cooled to room temperature, obtaining UiO-67-SO2@ANF fibers by suction filtration; (3.4) Wash the UiO-67-SO2@ANF fiber three times with DMF and methanol respectively to remove unreacted impurities; then replace the solvent with distilled water to prepare the UiO-67-SO2@ANF fiber into a UiO-67-SO2@ANF fiber dispersion; (3.5) Take the UiO-67-SO2@ANF fiber dispersion, add aqueous silane solution and tert-butyl alcohol, stir, and obtain UiO-67-SO2@ANF fiber aerogel through freeze drying and thermal curing.

[0007] Preferably, in step (1.1), the alkaline solution is a strong sodium oxide solution with a concentration of 10-20 wt%; the ratio of the mass of the aramid fibrils to the volume of the alkaline solution is (1-3) g: (300-800) ml; and the mixture is refluxed in a constant temperature water bath at 70-90°C for 3-5 hours.

[0008] Preferably, in the step (1.2), the concentration of the aramid nanofiber solution is 0.3-0.6 wt%; the process of treating the aramid fibril solution with a high-pressure homogenizer includes: first using a ball valve to increase the pressure to 700-900 MPa and treating for 15-25 min; then using a flat valve to increase the pressure to 900-1100 MPa and treating for 20-40 min.

[0009] Preferably, in step (2), the concentration of the PA solution is 15-25wt.%; the ratio of the mass of the aramid nanofiber to the volume of the PA solution is (0.5-1.5)g: (200-400)ml; stirring is performed in a water bath at 40°C for 2 h; The concentration of the ANF aqueous dispersion is 0.2-0.5 wt %.

[0010] Preferably, in step (3.1), the concentration of the ANF / DMF dispersion is 0.2-0.5wt%; Preferably, in the step (3.2), the mass ratio of trifluoroacetic acid to zirconium salt is (0.8-1.2):(4-6).

[0011] Preferably, in the step (3.3), the reaction temperature in the reactor is 110-130° C. and the reaction time is 10-14 h; and in the step (3.4), the concentration of the UiO-67-SO2@ANF fiber dispersion is 0.2-0.5 wt %.

[0012] Preferably, in the step (3.5), the volume of the UiO-67-SO2@ANF fiber dispersion, the mass of the aqueous silane solution and the volume ratio of the tert-butyl alcohol are: (8-12) mL: (0.01-0.05) g: (0.5-1.5) ml; the freeze-drying temperature is -60--40°C, and the time is 30-40 h; the thermal curing temperature is 160-200°C, and the time is 3-8 min.

[0013] The present invention also provides the use of the UiO-67-SO2@ANF fiber aerogel in the preparation of carbon dioxide separation and / or adsorption materials.

[0014] Compared with the prior art, the advantages and positive effects of the present invention include: (1) Compared with the traditional method of using potassium hydroxide (KOH) and 2-methyl sulfoxide (DMSO) to first deprotonate the aramid primary fiber and then use water as a proton donor to reduce it to obtain ANF, the present application adopts a high-pressure homogenization process to convert micron-sized aramid fibers into aramid nanofibers ANF, which can realize the batch preparation of ANF without the use of organic solvents. The ANF production efficiency is high and it is safe, environmentally friendly and pollution-free.

[0015] (2) Phosphoric acid treatment of ANF can expose a large number of active groups (amino and carboxyl groups) on the surface of ANF, thereby allowing the carboxyl groups to react with metal Zr 4+ A strong interfacial hydrogen bond is formed between them, and finally UiO-67-SO2 is uniformly and heavily loaded on the ANF surface, which can better promote the in situ growth of UiO-67-SO2 on the ANF surface.

[0016] (3) Through the fiber freeze-drying technology, by freezing the aqueous dispersion of UiO-67-SO2@ANF fibers, a block-shaped three-dimensional solid material (with ice crystals) can be obtained, which is conducive to the formation of a well-shaped ice crystal structure in the freezing process of the UiO-67-SO2@ANF fiber dispersion; then after the drying process, the ice crystals will sublimate, and the pores of the UiO-67-SO2@ANF fiber aerogel will be formed where the ice crystals exist, so that the aerogel forms a three-dimensional porous structure, giving the aerogel excellent mechanical properties, such as compression-rebound properties; after 800 compression-rebound test tests, the UiO-67-SO2@ANF fiber aerogel can still maintain a complete aerogel morphology.

[0017] (4) The UiO-67-SO2@ANF fiber aerogel of the present invention has a three-dimensional multi-level pore structure integrating macropores, mesopores and micropores, wherein the macropores and mesopores formed by the three-dimensional interconnected fiber network can serve as continuous long-range gas transmission channels, effectively improving the efficient diffusion of gas molecules inside it; and the UiO-67-SO2 distributed in the three-dimensional nanofiber network channel retains an open microporous structure, which can provide more contact area, active sites and transmission channels for CO2, thereby improving its adsorption capacity for CO2; at the same time, the hydrophobic micropores can also limit H2O molecules and promote the adsorption of CO2 molecules into the interior of the UiO-67-SO2 fiber aerogel.

[0018] (5) The MOF precursors of the present application include zirconium chloride (ZrCl4) and dibenzo[b,d]thiophene-3,7-dicarboxylic acid-5,5-dione (H2DTDAO). H2DTDAO has a sulfone functional group (O=S=O functional group), which is beneficial to promote the adsorption of CO2 by UiO-67-SO2@ANF fiber aerogel. CO2 molecules have three adsorption sites in the UiO-67-SO2 structural unit, including Zr 4+Molecular dynamics calculations show that for the UiO-67-SO2 structural unit, the static adsorption energy at O=S=O is 0.268 eV, which is significantly higher than that of the Zr4+ cluster (0.226 eV) and the benzene ring (0.183 eV), indicating that the introduction of O=S=O functional groups can promote the affinity of UiO-67-SO2@ANF aerogel for CO2, which is beneficial to promote the adsorption of CO2 by UiO-67-SO2@ANF fiber aerogel.

[0019] After reading the specific embodiments of the present invention in conjunction with the accompanying drawings, other features and advantages of the present invention will become more clear. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the SEM image of the UiO-67-SO2@ANF fiber aerogel of Example 1; Figure 2 This is a stress-strain curve of the UiO-67-SO2@ANF fiber aerogel of Example 1 measured by 800 cycles of compression-rebound test under the test condition of 50% deformation; Figure 3 This is a pore size distribution test diagram of the UiO-67-SO2@ANF fiber aerogel of Example 1; Figure 4 This is the SEM image of the ANF fiber aerogel of Comparative Example 1; Figure 5 This is a test graph of CO2 adsorption capacity of UiO-67-SO2@ANF fiber aerogel of Example 1 and ANF fiber aerogel of Comparative Example 1 at 25°C; Figure 6 These are the XRD test graphs of the UiO-67-SO2@ANF fiber aerogel of Example 1 and the ANF fiber aerogel and UiO-67-SO2 crystals of Comparative Example 1. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Meanwhile, after reading the present invention, those skilled in the art may make various modifications or changes to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

[0022] The UiO-67-SO2@ANF fiber aerogel of the present invention comprises a MOF precursor and aramid nanofibers, wherein the MOF precursor comprises a zirconium salt and dibenzo[b,d]thiophene-3,7-dicarboxylic acid-5,5-dione H2DTDAO.

[0023] The mass ratio of zirconium salt, H2DTDAO and ANF is (0.8-1.2): (1.8-2.2): (0.8-1.2), which can obtain UiO-67-SO2 particles of appropriate particle size, effectively avoiding the stacking distribution of Ui UiO-67-SO2 particles on the ANF surface, making the UiO-67-SO2 particles uniformly loaded on the ANF surface, effectively increasing the specific surface area of ​​UiO-67-SO2@ANF fiber aerogel, which is beneficial to CO2 gas transfer, thereby increasing its adsorption capacity for CO2.

[0024] The UiO-67-SO2@ANF fiber aerogel of the present invention has excellent thermal insulation performance, and the thermal conductivity at 25°C can be as low as 28 mW / mk.

[0025] The specific surface area of ​​the UiO-67-SO2@ANF fiber aerogel of the present invention is 500-700 m 2 / g, pore volume 0.5-0.8 cm 3 / g, and the average pore size is 0.4-1nm.

[0026] Preferably, the specific surface area of ​​the UiO-67-SO2@ANF fiber aerogel of the present invention is 600-680 m 2 / g, pore volume is 0.5-0.7cm 3 / g, and the average pore size is 0.4-0.6nm.

[0027] The UiO-67-SO2@ANF fiber aerogel of the present invention has a high specific surface area, a porous structure, and a high porosity, and can provide more active sites and transfer channels for CO2, thereby improving its adsorption capacity for CO2.

[0028] The UiO-67-SO2@ANF fiber aerogel of the present invention has excellent compressive elasticity, with a maximum compressive stress of 14.24 kPa. After 800 compression cycle tests, the plastic deformation is only 5.26%, the maximum compressive stress loss is 4.13%, the Young's modulus loss is only 4.29%, and the energy loss factor loss is only 16.46%.

[0029] The preparation method of the UiO-67-SO2@ANF fiber aerogel of the present invention comprises the following steps: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Cut the aramid fibrils into pieces, add them into an alkaline solution, and reflux them in a constant temperature water bath at 70-90°C for 3-5 hours. After the solution is cooled, filter and wash the solution with distilled water until it is neutral to obtain an aramid fibril solution; The aramid fibrils selected in the present invention may be para-aramid PPTA fibers. The para-aramid PPTA fibers have an obvious skin-core structure and can be easily cracked into nanofibers.

[0030] The aramid fibrils may also be other aramid fibers commonly used in the technical field, and are not specifically limited here.

[0031] The alkaline solution selected in the present invention can be a sodium hydroxide solution, which is not specifically limited herein.

[0032] The purpose of the present invention to perform alkali treatment on aramid fibrils is that aramid fibers have a distinct skin-core structure, that is, the fiber core layer has a higher molecular chain orientation and a higher crystallinity, while the fiber cortex has a lower crystallinity. After alkali treatment, the amide bonds on the surface of the aramid fibers will be hydrolyzed, so that the surface of the aramid fibers acquires electronegativity, that is, the charges on the surface of the aramid fibers repel each other, which is beneficial to the fiber splitting; at the same time, the alkali solution can damage the cortex of the aramid fibers to a certain extent. In other words, after being treated with an alkali solution, the aramid fibrils are more easily cracked, which is more conducive to the transformation into nanofibers. In the subsequent high-pressure homogenization process, the cortex of the aramid fibers will be further destroyed and cracked, which will make it easier to crack into nanofibers.

[0033] If the concentration of the alkali solution is too high, the high-concentration alkali solution will cause serious corrosion damage to the aramid fibrils; if the concentration of the alkali solution is too low, the low-concentration alkali solution cannot make the aramid fiber surface obtain effective electronegativity. After the subsequent high-pressure homogenization treatment, the aramid fiber cannot be effectively cracked into nanofibers, and the diameter distribution of the obtained aramid fiber is uneven, and the aramid fiber has an irregular shape.

[0034] The concentration of the alkaline solution selected in the present invention is 10-20wt%. Within this concentration range, the aramid fibrils will not be corroded and damaged, and the surface of the aramid fibers can obtain effective electronegativity. After subsequent high-pressure homogenization treatment, the aramid fibers can be effectively cracked into nanofibers. The obtained aramid fibers have uniform diameter distribution and regular morphology.

[0035] Preferably, the concentration of the alkaline solution selected in the present invention is 15wt%, the aramid fibrils will not be corroded and damaged, and the aramid fiber surface can obtain effective electronegativity. After subsequent high-pressure homogenization treatment, the aramid fibers can be effectively cracked into nanofibers, and the obtained aramid fibers have uniform diameter distribution and regular morphology.

[0036] The ratio of the mass of the aramid fibrils to the volume of the alkaline solution is (1-3) g: (300-800) ml, and preferably, the ratio of the mass of the aramid fibrils to the volume of the alkaline solution is 2 g: 500 ml; the amide bonds on the surface of the aramid fibers can be fully hydrolyzed without causing corrosion damage to the aramid fibrils, thereby ensuring that the surface of the aramid fibers obtains effective electronegativity, making it easier for the aramid fibers to be cleaved during the subsequent high-pressure homogenization process, thereby obtaining aramid fibers with uniform diameter distribution and regular fiber morphology.

[0037] (1.2) High-pressure homogenization treatment: using a high-pressure homogenizer to treat the aramid fibril solution to obtain an aramid nanofiber solution; filtering the aramid nanofiber solution to remove water to obtain aramid nanofibers; The process of treating the aramid fibril solution with a high-pressure homogenizer includes: first using a ball valve to gradually increase the pressure to 700-900 MPa for 15-25 min; then using a flat valve to gradually increase the pressure to 900-1100 MPa for 20-40 min.

[0038] The ball valve can be used to perform rough processing on the aramid fibrils, cut the aramid fibrils, and reduce the diameter and length of the aramid fibrils.

[0039] The flat valve can be used to perform fine processing on the aramid fibrils, shear the aramid fibrils, and further reduce the diameter and length of the aramid fibrils.

[0040] The fiber diameter after flat valve treatment is smaller than that after ball valve treatment, and the fiber diameter distribution will be more uniform, which is conducive to obtaining aramid nanofibers.

[0041] The invention processes aramid fibrils by a high-pressure homogenization method, so that the aramid fibrils are cracked into nanofibers, which is conducive to realizing the mass production of aramid nanofibers, does not require the use of organic solvents, and is safe, environmentally friendly and pollution-free.

[0042] The concentration of the aramid nanofiber solution is 0.3-0.6wt%, preferably, the concentration of the aramid nanofiber solution is 0.4wt%, which can help to filter out the water from the solution, thereby facilitating the acquisition of pure aramid nanofibers.

[0043] (2) Preparation of ANF aqueous dispersion Phosphoric acid PA treatment: the aramid nanofibers are added to the PA solution and stirred for 2 h in a 40°C water bath; then the ANF is washed with distilled water until it is neutral and prepared into an ANF aqueous dispersion; After phosphoric acid treatment, an affinity substitution reaction and / or hydrolysis reaction can occur between phosphoric acid and aramid nanofibers ANF, which can expose a large number of active groups (amino and carboxyl groups) on the surface of ANF. The active groups (amino and carboxyl groups) on the surface of ANF can react with the metal Zr in the subsequent step (3.2). 4+ A strong interfacial hydrogen bond is formed between them, and finally the UiO-66-NH2-F4 particles are uniformly and heavily loaded on the ANF surface.

[0044] The concentration of the PA solution is 15-25wt%, preferably, the concentration of the PA solution is 20wt%, which can cause a large number of active groups (amino and carboxyl groups) to be fully exposed on the surface of the ANF, which is beneficial for the uniform and large-scale loading of UiO-66-NH2-F4 particles on the surface of the ANF, and will not cause corrosion damage to the ANF fibers.

[0045] The ratio of the mass of aramid nanofibers to the volume of PA solution is (0.5-1.5) g: (200-400) ml; this can promote the full hydrolysis of ANF, so that a large number of active groups (amino and carboxyl groups) are fully exposed on the surface of ANF, which is beneficial to the uniform and large-scale loading of UiO-66-NH2-F4 particles on the surface of ANF without causing corrosion damage to the ANF fibers.

[0046] The concentration of ANF aqueous dispersion is 0.2-0.5wt%, preferably, the concentration of ANF aqueous dispersion is 0.3-0.4wt%, which is beneficial to improve the specific surface area, porosity and mechanical properties of fiber aerogel. Specifically, the fiber aerogel prepared by freeze-drying and heat curing treatment of ANF dispersion of this concentration can have the characteristics of light weight and excellent mechanical properties. If the concentration is further increased, the density of fiber aerogel prepared by the same volume of aqueous dispersion will be large, and the structure will be denser, resulting in a decrease in the porosity and specific surface area of ​​the fiber aerogel; at the same time, a high MOF content will cause the aerogel to become more brittle, which will eventually lead to a decrease in the mechanical properties of the fiber aerogel.

[0047] (3) Preparation of UiO-67-SO2@ANF fiber aerogel (3.1) Place the ANF aqueous dispersion in N, N-dimethylformamide (DMF) to prepare an ANF / DMF dispersion; The concentration of ANF / DMF dispersion is 0.2-0.5wt%, preferably, the concentration of ANF / DMF dispersion is 0.3-0.4wt%, which is beneficial to improve the specific surface area, porosity and mechanical properties of fiber aerogel. Specifically, the fiber aerogel prepared by freeze-drying and heat curing treatment of ANF dispersion of this concentration can have the characteristics of light weight and excellent mechanical properties. If the concentration of ANF / DMF dispersion is too high, the density of fiber aerogel prepared by the same volume of water dispersion will be large, and the structure will be denser, resulting in a decrease in the porosity and specific surface area of ​​the fiber aerogel; at the same time, if the concentration of ANF / DMF dispersion is too high, the MOF content is high, which will cause the aerogel to become more brittle, and ultimately lead to a decrease in the mechanical properties of the fiber aerogel.

[0048] (3.2) Weigh zirconium salt ZrCl4 and add it to the ANF / DMF dispersion, stirring until it is completely dissolved; then add H2DTDAO and trifluoroacetic acid TFA, continue stirring, and obtain a mixed solution; The role of adding zirconium salt first: After ANF is treated with PA, a large number of carboxyl functional groups will be generated on the surface of the fiber ANF, and the metal zirconium ions will produce metal complexation with the carboxyl groups, thereby inducing the metal zirconium ions to adsorb to the ANF surface. With the addition of the ligand H2DTDAO later, H2DTDAO will spontaneously combine with the metal zirconium ions, thereby in situ assembling into UiO-67-SO2 on the ANF surface, which is conducive to the uniform and large-scale loading of UiO-67-SO2 on the ANF surface.

[0049] H2DTDAO has sulfone functional groups (O=S=O functional groups), which is beneficial to promote the adsorption of CO2 by UiO-67-SO2@ANF fiber aerogel. CO2 molecules have three adsorption sites in the UiO-67-SO2 structural unit, including: Zr 4+ Molecular dynamics calculations show that for the UiO-67-SO2 structural unit, the static adsorption energy at O=S=O is 0.268 eV, which is significantly higher than that of Zr 4+ The static adsorption energies of clusters (0.226 eV) and benzene rings (0.183 eV) indicate that the introduction of O=S=O functional groups can promote the affinity of UiO-67-SO2@ANF fiber aerogel for CO2, which is beneficial to promote the adsorption of CO2 by UiO-67-SO2@ANF fiber aerogel and improve the adsorption capacity of CO2.

[0050] The role of trifluoroacetic acid is to promote better crystallization of UiO-67-SO2, which is beneficial for it to present a better UiO-67-SO2 crystal structure.

[0051] The mass ratio of trifluoroacetic acid to zirconium salt is (0.8-1.2):(3-6). Preferably, the mass ratio of trifluoroacetic acid to zirconium salt is 1:5, which can promote better crystallization of UiO-67-SO2 and help it present a good crystal structure and crystal morphology.

[0052] (3.3) transferring the mixed solution to a reactor for reaction, and after the reaction is completed and cooled to room temperature, obtaining UiO-67-SO2@ANF fibers by suction filtration; In the reactor, the reaction temperature is 110-130°C and the reaction time is 10-14h.

[0053] (3.4) Wash the UiO-67-SO2@ANF fiber three times with DMF and methanol respectively to remove unreacted impurities; then replace the solvent with distilled water to prepare the UiO-67-SO2@ANF fiber into a UiO-67-SO2@ANF fiber dispersion; The concentration of the UiO-67-SO2@ANF fiber dispersion is 0.2-0.5wt%, preferably, the concentration of the UiO-67-SO2@ANF fiber dispersion is 0.3-0.4wt%, which is beneficial to improve the specific surface area, porosity and mechanical properties of the fiber aerogel. Specifically, the fiber aerogel prepared by the ANF dispersion of this concentration after subsequent freeze-drying and heat curing treatment can have the characteristics of light weight and excellent mechanical properties. If the concentration of the UiO-67-SO2@ANF fiber dispersion is too high, the density of the fiber aerogel prepared by the same volume of water dispersion will be large, and the structure will be more compact, resulting in a decrease in the porosity and specific surface area of ​​the fiber aerogel; at the same time, if the concentration of the UiO-67-SO2@ANF fiber dispersion is too high, the MOF content is high, which will cause the aerogel to become more brittle, and ultimately lead to a decrease in the mechanical properties of the fiber aerogel.

[0054] (3.5) Take the UiO-67-SO2@ANF fiber dispersion, add aqueous silane solution and tert-butyl alcohol, stir, and obtain UiO-67-SO2@ANF fiber aerogel through freeze drying and thermal curing.

[0055] The volume of UiO-67-SO2@ANF fiber dispersion, the mass of aqueous silane solution and the volume ratio of tert-butanol are: (8-12) mL: (0.01-0.05) g: (0.5-1.5) ml; on the one hand, tert-butanol can maximize the promotion of UiO-67-SO2@ANF fiber dispersion to form a well-formed ice crystal structure and ice crystal morphology during the freezing process; on the other hand, it can ensure that the aqueous silane can be completely thermally cured, so that it can effectively promote the bonding between fibers and ensure that the UiO-67-SO2@ANF fiber aerogel obtains excellent compression-rebound properties.

[0056] The freeze-drying temperature is -60--40℃, and the time is 30-40 hours; the thermal curing temperature is 160-200℃, and the time is 3-8 minutes.

[0057] The role of tert-butanol: By adding tert-butanol to the UiO-67-SO2@ANF fiber dispersion, it is beneficial to promote the formation of a good ice crystal structure and ice crystal morphology in the freezing process of the UiO-67-SO2@ANF fiber dispersion; after the drying process, the ice crystals will sublimate, and the pores of the UiO-67-SO2@ANF fiber aerogel will be formed where the ice crystals exist, and finally a block-shaped three-dimensional structure of the UiO-67-SO2@ANF fiber aerogel is obtained, so that the aerogel has a three-dimensional multi-level pore structure, giving it excellent mechanical properties, such as compression-rebound properties. If tert-butanol is not added and the aqueous dispersion of the UiO-67-SO2@ANF fiber is directly frozen, the size of the ice crystals will be abnormally disordered, resulting in the final UiO-67-SO2@ANF fiber aerogel having very disordered pores and failing to give it excellent mechanical properties.

[0058] Purpose of freeze-drying: By freezing the aqueous dispersion of UiO-67-SO2@ANF fibers, a solid material with a three-dimensional structure (with ice crystals) can be obtained, which is conducive to the formation of a well-shaped ice crystal structure in the freezing process of the UiO-67-SO2@ANF fiber dispersion; and then through the drying process, the ice crystals will sublime, and the pores of the UiO-67-SO2@ANF fiber aerogel will be formed where the ice crystals exist, so that the aerogel forms a three-dimensional porous structure, giving the aerogel excellent mechanical properties, such as compression-rebound properties.

[0059] The role of water-based silane: By subjecting the freeze-dried UiO-67-SO2@ANF fiber aerogel to high-temperature heat treatment, the silane in it will be thermally cured, thereby promoting adhesion between fibers, and ultimately giving the UiO-67-SO2@ANF fiber aerogel excellent mechanical properties, such as compression-rebound properties. If silane is not added, the UiO-67-SO2@ANF fiber aerogel will not have elasticity after compression.

[0060] Purpose of thermal curing: By subjecting the freeze-dried UiO-67-SO2@ANF fiber aerogel to high-temperature heat treatment, the silane therein will be thermally cured, thereby promoting bonding between the fibers, and ultimately giving the UiO-67-SO2@ANF fiber aerogel excellent mechanical properties (compression-rebound properties).

[0061] The beneficial technical effects of this application include: (1) Compared with the traditional method of using potassium hydroxide (KOH) and 2-methyl sulfoxide (DMSO) to first deprotonate the aramid primary fiber and then use water as a proton donor to reduce it to obtain ANF, the present application adopts a high-pressure homogenization process to convert micron-sized aramid fibers into aramid nanofibers ANF, which can realize the batch preparation of ANF without the use of organic solvents. The ANF production efficiency is high and it is safe, environmentally friendly and pollution-free.

[0062] (2) Phosphoric acid treatment of ANF can expose a large number of active groups (amino and carboxyl groups) on the surface of ANF, thereby allowing the carboxyl groups to react with metal Zr 4+ A strong interfacial hydrogen bond is formed between them, and finally UiO-67-SO2 is uniformly and heavily loaded on the ANF surface, which can better promote the in situ growth of UiO-67-SO2 on the ANF surface.

[0063] (3) Through the fiber freeze-drying technology, by freezing the aqueous dispersion of UiO-67-SO2@ANF fibers, a block-shaped three-dimensional solid material (with ice crystals) can be obtained, which is conducive to the formation of a well-shaped ice crystal structure in the freezing process of the UiO-67-SO2@ANF fiber dispersion; then after the drying process, the ice crystals will sublimate, and the pores of the UiO-67-SO2@ANF fiber aerogel will be formed where the ice crystals exist, so that the aerogel forms a three-dimensional porous structure, giving the aerogel excellent mechanical properties, such as compression-rebound properties; after 800 compression-rebound test tests, the UiO-67-SO2@ANF fiber aerogel can still maintain a complete aerogel morphology.

[0064] (4) The UiO-67-SO2@ANF fiber aerogel of the present invention has a three-dimensional multi-level pore structure integrating macropores, mesopores and micropores, wherein the macropores and mesopores formed by the three-dimensional interconnected fiber network can serve as continuous long-range gas transmission channels, effectively improving the efficient diffusion of gas molecules inside it; and the UiO-67-SO2 distributed in the three-dimensional nanofiber network channel retains an open microporous structure, which can provide more contact area, active sites and transmission channels for CO2, thereby improving its adsorption capacity for CO2; at the same time, the hydrophobic micropores can also limit H2O molecules and promote the adsorption of CO2 molecules into the interior of the UiO-67-SO2 fiber aerogel.

[0065] (5) The MOF precursors of the present application include zirconium chloride (ZrCl4) and dibenzo[b,d]thiophene-3,7-dicarboxylic acid-5,5-dione (H2DTDAO). H2DTDAO has a sulfone functional group (O=S=O functional group), which is beneficial to promote the adsorption of CO2 by UiO-67-SO2@ANF fiber aerogel. CO2 molecules have three adsorption sites in the UiO-67-SO2 structural unit, including Zr 4+ Molecular dynamics calculations show that for the UiO-67-SO2 structural unit, the static adsorption energy at O=S=O is 0.268 eV, which is significantly higher than that of the Zr4+ cluster (0.226 eV) and the benzene ring (0.183 eV), indicating that the introduction of O=S=O functional groups can promote the affinity of UiO-67-SO2@ANF fiber aerogel for CO2, which is beneficial to promote the adsorption of CO2 by UiO-67-SO2@ANF fiber aerogel.

[0066] Therefore, the UiO-67-SO2@ANF fiber aerogel of the present application has a strong affinity for CO2 molecules and can improve the CO2 adsorption efficiency and adsorption performance.

[0067] The UiO-67-SO2@ANF fiber aerogel of the present invention can be used to prepare carbon dioxide separation and / or adsorption materials. Example

[0068] The preparation method of the UiO-67-SO2@ANF fiber aerogel of this embodiment includes the following steps: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Weigh 2 g of aramid fibrils and cut them into pieces. Add them into 500 mL of 15 wt% sodium hydroxide (NaOH) alkaline solution and reflux them in a constant temperature water bath at 80 °C for 4 h. After the solution is cooled, filter it with distilled water and wash it until it is neutral to obtain an aramid fibril solution. (1.2) High-pressure homogenization treatment: The aramid fibril solution is treated by a high-pressure homogenizer to obtain an aramid nanofiber solution with a concentration of 0.4 wt %; the aramid nanofiber solution is filtered and water is removed to obtain aramid nanofibers; The process of treating the aramid fibril solution with a high-pressure homogenizer includes: first using a ball valve to gradually increase the pressure to 800 MPa for 20 minutes; then using a flat valve to gradually increase the pressure to 1000 MPa for 30 minutes.

[0069] (2) Preparation of ANF aqueous dispersion Phosphoric acid PA treatment: 0.1 g ANF was added to 30 mL of 20 wt% PA solution and stirred in a 40 ℃ water bath for 2 h; then the ANF was washed with distilled water until neutral and prepared into an ANF aqueous dispersion with a mass fraction of 0.3 wt%.

[0070] (3) Preparation of UiO-67-SO2@ANF fiber aerogel (3.1) Place 30 mL of 0.3 wt% ANF aqueous dispersion in N, N-dimethylformamide (DMF) to prepare a 0.3 wt% ANF / DMF dispersion; (3.2) Weigh 0.09 g of zirconium salt ZrCl4 into the ANF / DMF dispersion and stir for 15 min until it is completely dissolved; then add 0.18 g H2DTDAO and 0.018 g trifluoroacetic acid TFA and continue stirring for 15 min to obtain a mixed solution; (3.3) The mixed solution was transferred to a reactor and reacted at 120° C. for 12 h. After the reaction was completed and cooled to room temperature, UiO-67-SO2@ANF fibers were obtained by suction filtration. (3.4) Wash the UiO-67-SO2@ANF fiber three times with DMF and methanol respectively to remove unreacted impurities; then replace the solvent with distilled water to prepare the UiO-67-SO2@ANF fiber into a UiO-67-SO2@ANF fiber dispersion with a concentration of 0.3wt%; (3.5) Take 10 ml of the above UiO-67-SO2@ANF fiber dispersion, add 0.03 g of aqueous silane solution and 1 mL of tert-butyl alcohol, stir for 15 min, and then freeze-dry and heat-cure to obtain UiO-67-SO 2@ ANF ​​fiber aerogel. Freeze drying temperature is -50℃, time is 36 h; thermal curing temperature is 180℃, time is 5 min.

[0071] The SEM test results of the UiO-67-SO2@ANF fiber aerogel in Example 1 are as follows: Figure 1 As shown. Figure 1 It can be seen that after UiO-67-SO2 is in situ assembled on the ANF surface, evenly distributed particles of UiO-67-SO2 (ie, MOF) appear on the surface of UiO-67-SO2@ANF fiber aerogel.

[0072] The UiO-67-SO2@ANF fiber aerogel of this embodiment was subjected to 800 cycles of compression-rebound test under the test condition of 50% deformation. The measured stress-strain curve is shown in the figure below: Figure 2 As shown. Figure 2It can be explained that the UiO-67-SO2@ANF fiber aerogel of this embodiment can still maintain the complete aerogel morphology structure after 800 cycles of compression-rebound test, indicating that the UiO-67-SO2@ANF fiber aerogel of Example 1 has excellent compression rebound performance.

[0073] The MOF loading amount of the UiO-67-SO2@ANF fiber aerogel of this embodiment was calculated. By weighing on a balance, it can be calculated that the MOF loading amount on the surface of the UiO-67-SO2@ANF fiber aerogel is 58.23%.

[0074] The pore size distribution of the UiO-67-SO2@ANF fiber aerogel in this embodiment was tested. Figure 3 (a) The pore size distribution curve calculated by mercury intrusion method shows that the macropore diameter of UiO-67-SO2@ANF fiber aerogel is distributed between 10-110 μm; Figure 3 (b) The pore size distribution curve calculated by the BJH model shows that the pore sizes of the micropores and mesopores of UiO-67-SO2@ANF fiber aerogel are concentrated between 0.3-4 nm. This shows that UiO-67-SO2@ANF fiber aerogel has an obvious three-dimensional multi-level pore structure, in which the macropores and mesopores are conducive to promoting the transmission and diffusion of CO2 gas molecules, while the micropores can effectively improve the adsorption of CO2 gas molecules by UiO-67-SO2@ANF fiber aerogel.

[0075] The specific surface area, pore volume and average pore size can be obtained by using a fully automatic specific surface area and porosity analyzer. The specific surface area of ​​the UiO-67-SO2@ANF fiber aerogel in Example 1 is 670.36 m 2 / g, pore volume 0.521cm 3 / g, and the average pore size is 0.472nm. The UiO-67-SO2@ANF fiber aerogel of Example 1 has a high specific surface area, a porous structure, and a high porosity, which can provide more active sites and transfer channels for CO2, thereby improving its adsorption capacity for CO2.

[0076] Comparative Example 1 The preparation method of the ANF fiber aerogel of this comparative example includes the following preparation process: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Weigh 2 g of aramid fibrils and cut them into pieces. Add them into 500 mL of 15 wt.% sodium hydroxide (NaOH) alkaline solution and reflux them in a constant temperature water bath at 80 °C for 4 h. After the solution is cooled, filter it with distilled water and wash it until it is neutral to obtain an aramid fibril solution. (1.2) High-pressure homogenization treatment: The aramid fibril solution is treated by a high-pressure homogenizer to obtain an aramid nanofiber solution with a concentration of 0.4 wt %; the aramid nanofiber solution is filtered and water is removed to obtain aramid nanofibers; The process of treating the aramid fibril solution with a high-pressure homogenizer includes: first using a ball valve to gradually increase the pressure to 800 MPa for 20 minutes; then using a flat valve to gradually increase the pressure to 1000 MPa for 30 minutes.

[0077] (2) Preparation of ANF fiber aerogel Take 10 ml of the above ANF fiber dispersion, add 0.03 g of aqueous silane solution and 1 mL of tert-butyl alcohol, stir for 15 min, and then freeze-dry and heat-cure to obtain ANF fiber aerogel. The freeze-drying temperature is -50 ° C, the time is 36 h; the heat-cure temperature is 180 ° C, and the time is 5 min.

[0078] Figure 4 This is the SEM image of the ANF fiber aerogel prepared in this comparative example 1. Figure 4 It can be shown that the surface of the ANF fiber aerogel in Comparative Example 1 is flat and smooth, without loading other substances, and the diameter of the ANF fiber is concentrated in the range of 30-180 nm.

[0079] The CO2 adsorption capacity of the UiO-67-SO2@ANF fiber aerogel of Example 1 and the ANF fiber aerogel of Comparative Example 1 at 25°C was tested. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the adsorption capacity of UiO-67-SO2@ANF fiber aerogel in Example 1 for CO2 is much greater than the adsorption capacity of ANF fiber aerogel in Comparative Example 1 for CO2.

[0080] The XRD test results of the UiO-67-SO2@ANF fiber aerogel of Example 1 and the ANF fiber aerogel and UiO-67-SO2 crystal of Comparative Example 1 are as follows: Figure 6 As shown. Figure 6 It can be seen that the particles on the fiber surface of UiO-67-SO2@ANF fiber aerogel are UiO-67-SO2, indicating that UiO-67-SO2 particles (i.e., MOF) are loaded on the ANF surface.

[0081] The above embodiments are only used to illustrate the equivalent replacement of the technical lines of the present invention; these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions claimed to be protected by the present invention, nor do they limit them; although the present invention has been described in detail with reference to the above embodiments, it is still possible for ordinary technicians in this field to modify the technical solutions recorded in the above embodiments, or to improve the spirit and scope of some of the technical features therein.

Claims

1. A UiO-67-SO2@ANF fiber aerogel, characterized in that: include: A MOF precursor and aramid nanofibers ANF, wherein the MOF precursor comprises a zirconium salt and dibenzo[b,d]thiophene-3,7-dicarboxylic acid-5,5-dione H2DTDAO; The mass ratio of zirconium salt, H2DTDAO and ANF is (0.8-1.2): (1.8-2.2): (0.8-1.2); The specific surface area of ​​the UIO-67-SO2@ANF fiber aerogel is 500-700 m 2 / g, pore volume 0.5-0.8 cm 3 / g, and the average pore size is 0.4-1nm.

2. The method for preparing the UiO-67-SO2@ANF fiber aerogel according to claim 1, characterized in that: include: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Cut the aramid fibrils into pieces, add them into an alkaline solution, reflux them in a constant temperature water bath, and after the solution is cooled, filter and wash the solution with distilled water until it is neutral to obtain an aramid fibril solution; (1.2) High-pressure homogenization treatment: using a high-pressure homogenizer to treat the aramid fibril solution to obtain an aramid nanofiber solution; filtering the aramid nanofiber solution to remove water to obtain aramid nanofibers; (2) Preparation of ANF aqueous dispersion Phosphoric acid PA treatment: adding the aramid nanofibers to the PA solution and stirring under water bath conditions; then washing the solution with distilled water until it is neutral and preparing it into an ANF aqueous dispersion; (3) Preparation of UiO-67- SO2@ANF fiber aerogel (3.1) placing the ANF aqueous dispersion in N, N-dimethylformamide (DMF) to prepare an ANF / DMF dispersion; (3.2) adding zirconium salt to the ANF / DMF dispersion and stirring until it is completely dissolved; then adding H2DTDAO and trifluoroacetic acid TFA and continuing to stir to obtain a mixed solution; (3.3) transferring the mixed solution to a reactor for reaction, and after the reaction is completed and cooled to room temperature, obtaining UiO-67-SO2@ANF fibers by suction filtration; (3.4) Wash the UiO-67-SO2@ANF fiber three times with DMF and methanol respectively to remove unreacted impurities; then replace the solvent with distilled water to prepare the UiO-67-SO2@ANF fiber into a UiO-67-SO2@ANF fiber dispersion; (3.5) Take the UiO-67-SO2@ANF fiber dispersion, add aqueous silane solution and tert-butyl alcohol, stir, and obtain UiO-67-SO2@ANF fiber aerogel through freeze drying and thermal curing.

3. The method for preparing UiO-67-SO2@ANF fiber aerogel according to claim 2, characterized in that: In the step (1.1), the alkaline solution is a strong sodium oxide solution with a concentration of 10-20 wt%; The ratio of the mass of the aramid fiber to the volume of the alkaline solution is (1-3) g: (300-800) ml; Reflux in a constant temperature water bath at 70-90℃ for 3-5h.

4. The method for preparing the UiO-67-SO2@ANF fiber aerogel according to claim 2, characterized in that: In the step (1.2), the concentration of the aramid nanofiber solution is 0.3-0.6 wt %; The process of treating the aramid fiber solution with a high-pressure homogenizer includes: first using a ball valve to increase the pressure to 700-900 MPa for 15-25 min; then using a flat valve to increase the pressure to 900-1100 MPa for 20-40 min.

5. The method for preparing UiO-67-SO2@ANF fiber aerogel according to claim 2, characterized in that: In step (2), the concentration of the PA solution is 15-25wt.%; The ratio of the mass of the aramid nanofiber to the volume of the PA solution is (0.5-1.5) g: (200-400) ml; Stir in a 40 °C water bath for 2 h; The concentration of the ANF aqueous dispersion is 0.2-0.5 wt %.

6. The method for preparing the UiO-67-SO2@ANF fiber aerogel according to claim 2, characterized in that: In the step (3.1), the concentration of the ANF / DMF dispersion is 0.2-0.5wt%.

7. The method for preparing UiO-67-SO2@ANF fiber aerogel according to claim 2, characterized in that: In the step (3.2), the mass ratio of trifluoroacetic acid to zirconium salt is (0.8-1.2):(4-6).

8. The method for preparing UiO-67-SO2@ANF fiber aerogel according to claim 2, characterized in that: In the step (3.3), the reaction temperature in the reactor is 110-130°C and the reaction time is 10-14h; In the step (3.4), the concentration of the UiO-67-SO2@ANF fiber dispersion is 0.2-0.5wt%.

9. The method for preparing UiO-67-SO2@ANF fiber aerogel according to claim 2, characterized in that: In the step (3.5), the volume ratio of the UiO-67-SO2@ANF fiber dispersion, the mass of the aqueous silane solution and the volume ratio of the tert-butyl alcohol is: (8-12) mL: (0.01-0.05) g: (0.5-1.5) ml; The freeze-drying temperature is -60--40℃ and the time is 30-40 h; The thermal curing temperature is 160-200°C and the time is 3-8 minutes.

10. Use of the UiO-67-SO2@ANF fiber aerogel according to claim 1 in preparing carbon dioxide separation and / or adsorption materials.

Citation Information

Patent Citations

  • MOF-containing aramid fiber aerogel as well as preparation method and application thereof

    CN118772647A

  • Solid-state crystallization of metal organic frameworks within mesoporous materials methods and hybrid materials thereof

    US20190169036A1